Interpretations of “True Knowledge” in Zhuangzi’s Philosophy - Rongkun Zhang (Religions)
Genuine Humans can achieve a way of existence in harmony with the “Way of Heaven” and open up a meaningful world where Heaven and humanity are integrated. Therefore, the “Way of Heaven”, as the true source of value for true knowledge, highlights the “transcendental” aspect of true knowledge. On the other hand, true knowledge includes the compassionate understanding and sincere empathy of a Genuine Human towards the unavoidable fact of the human world, thereby manifesting its “practical” dimension in a harmonious sense.